Predictors of Lateral Compartment Joint Space Difference at a Minimum of Two Years after ACL Reconstruction: Data from the Moon Onsite Cohort. Issue 7 (18th July 2016) - Jones, Morgan H.; Reinke, Emily; Duryea, Jeffrey; Fleming, Braden C.; Obuchowski, Nancy; Winalski, Carl S.; Spindler, Kurt P.
Objectives: ACL reconstruction effectively restores knee stability and allows a return to athletic activities after ACL injury, but patients are still at higher risk of developing post-traumatic OA. Patient reported outcomes from the Multicenter Orthopaedic Outcomes Network (MOON) prospective longitudinal cohort of over 1500 patients undergoing ACL reconstruction showed no increase in OA symptoms (KOOS subscale) at 2 or 6 years after surgery. Therefore, identification of structural changes of OA that may precede the onset of symptoms is of critical importance for determining risk factors for the initiation and progression of post-traumatic OA in addition to measuring the effectiveness of potential disease-modifying treatments. One structural measure of OA is radiographic joint space width (JSW). We previously demonstrated that meniscus treatment and age predict narrower medial compartment JSW. Methods: 335 patients from the MOON cohort (154 males, 181 females, median age 18 years at the time of surgery) were recruited at a minimum of 2 years following surgery for on-site evaluations including bilateral metatarsophalangeal joint (MTP) radiographs to assess JSW. To minimize bias related to pre-existing knee injury or OA, subjects were 35 years or younger, were injured playing a sport, had primary ACL reconstruction without prior meniscus or articular cartilage surgery, did not undergo subsequent ACL revision, and had a surgically normal contralateral knee. Radiographic JSW was measured in the lateral compartment of both knees using a validated semiautomated method. The association of age, sex, BMI, meniscus treatment, and articular cartilage treatment with lateral compartment JSW differences (JSD) between the reconstructed and normal knees was examined using multivariable generalized linear models. The Holm-Bonferroni method was used to account for multiple comparisons. Results: The mean lateral compartment JSW was 7.73 mm and (95% CI 7.61-7.85 mm) for ACL reconstructed knees and 7.82 mm (95% CI 7.71-7.94 mm) for contralateral normal knees, with a mean JSD of 0.10 mm (p<0.01). A miltivariable generalized linear model was constructed which adjusted for age, gender, BMI, and baseline Marx activity level. Predictors of JSD that were statistically significant and predicted narrower JSW on the ACL reconstructed side included partial lateral meniscectomy (p<0.001), Marx activity level less than 16(p=0.002), and higer BMI (p=0.02). Graft source, cartilage injury, sex and lateral compartment articular carilage injury wer not significant. Model results are shown in the table. Conclusion: We found that radiographic lateral compartment JSW differences between reconstructed and normal knees could be detected 2 years after durgery in a cohort of patients with previously uninjured knees who sustained ACL tears and underwent subsequent ACL reconstruction. The model showed that parial lateral meniscectomy, lower Marx activity level, and higher BMI were associated with decreased joint space width. The reason that patients with lower activity levels at baseline have narrower lateral compartment JSW on their ACL reconstructed side is unclear and warrants further study.